A Meta-Analysis of the Effect of Private Tutoring on the Academic Achievement of Secondary School Students in India - Misra, Utkarsh; Trivedi, Tripta (JOURNAL OF INDIAN EDUCATION, 2026)
This study, aimed to conduct a meta analysis on the effectiveness of private tutoring on the academic achievement of students at the secondary stage in India. Fifteen data sets from seven studies published between 2000 and 2024, with a combined sample size of 7,961 students, were included. Using MetaEssentials software and a random effects model, the combined effect size was found to be 0.24, indicating a small positive effect of private tutoring on students’ scholastic gains. The findings suggest that while private tuition may offer a modest benefit, its overall contribution to enhancing academic performance is limited, challenging the often-held perception that private tutoring results in substantial gains in students’ academic achievement.